1986
DOI: 10.1080/00207598608247609
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐language Differences in Dichotic Listening*

Abstract: Greater right ear advantage in dichotic listening to English-spoken digits among English-speakers than among Japanese-and Hebrew-speakers (Hatta and Dimond 1981; Nachshon 1986) was attributed either to effects of lingustic properties of the respective native languages, or to the sequence of language acquisition. In order to evaluate the two alternative hypotheses, 112 English-Hebrew and 140 Hebrew-En&sh bilinguals recalled a series of three-digit dichotic sets. Differential ear advantages were expected on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…One possible reason for this finding may be that participants were trying to maintain and/or attend to information related to making the distance judgment. Distance cues in English speech may be more salient and easier to maintain because of their lexical and phonetic familiarity [27] , and may thus require less engagement of ACC (i.e., greater ACC activity is required to effectively process Bengali speech). Backwards speech may also show less engagement of ACC because information cannot be adequately maintained in working memory (backwards speech is harder to reproduce, and thus rehearse), and because selective attention may be less effective when lexical or phonetic familiarity cues are not contributing to auditory scene analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this finding may be that participants were trying to maintain and/or attend to information related to making the distance judgment. Distance cues in English speech may be more salient and easier to maintain because of their lexical and phonetic familiarity [27] , and may thus require less engagement of ACC (i.e., greater ACC activity is required to effectively process Bengali speech). Backwards speech may also show less engagement of ACC because information cannot be adequately maintained in working memory (backwards speech is harder to reproduce, and thus rehearse), and because selective attention may be less effective when lexical or phonetic familiarity cues are not contributing to auditory scene analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous study in a smaller sample using the same paradigm (Bless et al, 2013 ), we would expect to find differences in the REA between language groups. However, other studies using different dichotic listening paradigms (multiple responses per trial) have not found cross-cultural differences (Cohen, Levy, & McShane, 1989 ; Nachshon, 1986 ). In addition, we also expected the size of the REA to be modulated by sex (males > females), handedness (right-handers > left-handers) and age (increasing REA with age), as reported in previous studies (Hirnstein, Westerhausen, Korsnes, & Hugdahl, 2013 ; Hiscock, Inch, Jacek, Hiscock-Kalil, & Kalil, 1994 ; Hugdahl, 2003 ).…”
mentioning
confidence: 90%
“…Although this first cross-cultural study concerning the perception of emotional overtones of unfamiliar speech offers much suggestive evidence, it is too early to conclude that Japanese and Israelis differ in pattern of hemisphere function because the sample of the present study is not large enough. In light of previous data (Hatta and Nachshon 1986;Nachshon 1986) showing no significant differences between subjects of the two cultures in performance on lateralized tasks, any suggestion concerning cross-cultural differences between the two should be made with caution. More cross-cultural studies are indispensable in order to further explore the environmental effects on brain organization.…”
Section: Discussionmentioning
confidence: 88%
“…The notion that hemisphere function, especially hemispheric specialization, may vary across languages has recently gained considerable support (Hatta and Dimond 1981;Moss et al 1985;Tsao and Wu 1981). However, in two recent studies comparing Israeli and Japanese subjects (Hatta and Nachshon 1986;Nachshon 1986) no differences were found between the two groups in performance on lateralized tasks .…”
mentioning
confidence: 99%